Role of Medical Imaging in Cancers - Fanti, Stefano; Evangelista, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The issue of Cancers Journal entitled "Role of Medical Imaging in Cancers" presents a detailed summary of evidences about molecular imaging, including the role of computed tomography (CT), magnetic resonance imaging (MRI), single photon emission tomography (SPET) and positron emission tomography (PET) or PET/CT or PET/MR imaging in many type of tumors (i.e. sarcoma, prostate, breast and others), motivating the role of these imaging modalities in different setting of disease and showing the recent developments, in terms of radiopharmaceuticals, software and artificial intelligence in this field. The collection of articles is very useful for many specialists, because it has been conceived for a multidisciplinary point of view, in order to drive to a personalized medicine.